2021
DOI: 10.21037/apm-21-3549
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the clinical diagnosis and treatment of uveitis

Abstract: Background: Uveitis is a not uncommon potentially sight-threatening intraocular inflammatory disorder and a major cause of blindness worldwide. Early diagnosis and effective treatment are very important to reduce complications and protect vision.Methods: In a retrospective series, we enrolled 263 (390 eyes) consecutive uveitis patients, comprising 126 males and 137 females. The clinical types of uveitis, treatment efficacy, complications and visual prognosis were evaluated by detailed clinical examination, lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
4
3
0
Order By: Relevance
“…We conducted a descriptive study of the patients with NIU followed up in the multidisciplinary uveitis unit of our hospital. The results did not differ from those reported in other published series [ 25 , 26 , 27 , 28 ]. There was no significant difference in sex, the mean age at diagnosis was 42.8 years, and the most frequent cases were anterior (74.4%) as well as unilateral (76.1%) uveitis.…”
Section: Discussionsupporting
confidence: 53%
“…We conducted a descriptive study of the patients with NIU followed up in the multidisciplinary uveitis unit of our hospital. The results did not differ from those reported in other published series [ 25 , 26 , 27 , 28 ]. There was no significant difference in sex, the mean age at diagnosis was 42.8 years, and the most frequent cases were anterior (74.4%) as well as unilateral (76.1%) uveitis.…”
Section: Discussionsupporting
confidence: 53%
“…We conducted a descriptive study of the patients with NIU followed up in the multidisciplinary uveitis unit of our hospital. The results did not differ from those reported in other published series [25][26][27][28]. There was no significant difference in sex, the mean age at diagnosis was 42.8 years, and the most frequent cases were anterior (74.4%) as well as unilateral (76.1%) uveitis.…”
Section: Discussionsupporting
confidence: 46%
“…Uveitis is a common form of eye inflammation. Due to the complications, such as neovascularization and secondary intraocular pressure, uveitis is considered a major cause of eye damage [ 65 ]. Thuy et al found that MDS could efficiently detect abundant pathogens in the intraocular fluid of patients with uveitis.…”
Section: Applications Of Hts Technology In Ocular Diseasesmentioning
confidence: 99%